(untitled) (Bangladesh Critical Care Journal, 2020)
Background: Burn out is a common syndrome observed among health care workers in highly stressed environment of ICU. We investigated prevalence of burn out and its associated risk factors among doctors and nurses working in ICUs of Bangladesh. Methods: We conducted a cross sectional survey on 93 physicians and 247 nurses working in 12 ICUs of Bangladesh. Maslach Burn out Inventory-Human services Survey was used to measure Burn out outcome. Univariate and multivariate random effects logistic regression analysis of predictors for burnout as outcome measure among physicians and nurses were performed. Results: 21.3 % of all study physicians and nurses suffer moderate to high burn out. 51% of all study doctors and 87 % of all study nurses suffer from low burn out. For doctors working in ICU having a religious back ground, imbalance between professional working time and time for personal life, monthly salary, hours of sleep per day, years of working experience, percentage of work time spent in ICU and number of ICU patients cared for per day, no of stay-at-home night calls or night shifts per month at work appeared significantly associated with high burn out. For nurses having a religious back ground or belief, having child more than two, higher educational qualification (bachelor degree), low monthly salary; less hours per week engaged in charity work, low level of personal control over work, imbalanced work‑life, more than 26 work days per month, more frequent shifts in work, conflicts with colleagues all were associated with high burn out. Conclusion: Among all interventions, promoting reduction of work load and improving work-life balance need to be addressed as a priority in order to reduce burn out. Bangladesh Crit Care J March 2020; 8(1): 5-16